"Totemic species" can be an effective lens for engaging students with Indigenous knowledge and biodiversity conservation. Issue 4 (6th March 2023) - Ward, Natasha M.; Garrard, Georgia; Gregg, Emily A.; May, Benjamin; Wandin, Dave; Harrison, Micheal; Pascoe, Marnie; McConachie, Fiona; Moggridge, Bradley; Kusmanoff, Alex; Bekessy, Sarah A.
Abstract: We present the outcomes of a program designed to engage primary school students with both Indigenous knowledge and biodiversity conservation, through the lens of "Totemic" species. The program provided resources for genuine engagement with Traditional Owners, and for the coordinating teachers to dedicate time to curriculum development and delivery. The material was embedded within a cross‐school core curriculum topic (biology), presenting both Indigenous and Western knowledge in parallel. Students' understanding of ecology and conservation increased significantly post‐program, as did their cultural awareness and appreciation of traditional knowledge. Care for the totemic species was also shown to increase and enthusiasm for this approach to teaching science was expressed by students. The co‐benefits of this program include creating habitat for threatened species, improvements in the health and wellbeing of students through engagement with biodiversity and the potential for ecosystem services such as cooling of the school grounds. Effective ways of embedding cultural awareness and Indigenous knowledge into the Australian curriculum are urgently needed and it is our hope that this program provides evidence of effective ways of embedding these knowledges moving forward. Abstract : We present the outcomes of a program designed to engage primary school students with both Indigenous knowledge and biodiversity conservation, through the lens of "Totemic" species. The program provided resources for genuine engagement with Traditional Owners, and for the coordinating teachers to dedicate time to curriculum development and delivery. The material was embedded within a cross‐school core curriculum topic (biology), presenting both Indigenous and Western knowledge in parallel.